Electrospinning from a convex needle with multiple jet toward better controlling and enhanced production rate. Issue 40 (29th May 2019) - Jahan, Israt; Jadhav, Amit; Wang, Lijing; Wang, Xin
ABSTRACT: Multiple jet was successfully generated from a convex needle spinneret based on a conventional electrospinning setup. A convex channel was created in the front part of the needle to generate a limited free surface in the electrospinning process. A high flow rate was implemented with more than one polymer jet being produced, resulting in the production rate 2–3 times higher than conventional electrospinning. Finer nanofibers were produced from the convex needle when the applied voltage was 19 kV. The electric field intensity distribution of this spinneret was analyzed and compared with conventional needle spinneret by Comsol Multiphysics modeling. The research work has demonstrated that scaling up the production rate of nanofibers from needle‐based free surface electrospinning is possible. It will benefit further development of electrospinning with enhanced throughput and more precise controlling. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2019, 136, 48014. Abstract :